Stress evolution in restrained GGBFS concrete due to autogenous deformation: bayesian optimization of aging creep. (21st March 2022) - Liang, Minfei; Li, Zhenming; He, Shan; Chang, Ze; Gan, Yidong; Schlangen, Erik; Šavija, Branko
Highlights: Experiments of restrained stress development and autogenous deformation of concrete with high content of GGBFS were conducted. A computational framework for simulating the restrained stress development considering the influence of aging creep and shrinkage was built. Inverse modelling based on Bayesian optimization was conducted to efficiently optimize the utilized creep model. The aging creep of of GGBFS concrete with different w/b ratios were analyzed. Abstract: Stress evolution of restrained concrete is a significant direct index in early-age cracking (EAC) analysis of concrete. This study presents experiments and numerical modelling of the early-age stress evolution of Ground granulated blast furnace slag (GGBFS) concrete, considering the development of autogenous deformation and creep. Temperature Stress Testing Machine (TSTM) tests were conducted to obtain the autogenous deformation and stress evolution of restrained GGBFS concrete. By a self-defined material subroutine based on the Rate-type creep law, the FEM model for simulating the stress evolution in TSTM tests was established. By characterizing the creep compliance function with a 13-units continuous Kelvin chain, forward modelling was firstly conducted to predict the stress development. Then inverse modelling was conducted by Bayesian Optimization to efficiently modify the arbitrary assumption of the codes on the aging creep. The major findings of this study are as follows: 1) the high autogenous expansion of GGBFS induces compressive stress at first hours, but its value is low because of high relaxation and low elastic modulus; 2) The codes highly underestimated the early-age creep of GGBFS concrete. They performed well in prediction of stress after 200 h, but showed significant gaps in predictions of early-age stress evolution; 3) The proposed inverse modelling method with Bayesian Optimization can efficiently adjusted the aging terms which produced best modelling results. The adjusted creep compliance function of GGBFS showed a much faster aging speed at early ages than the one proposed by original codes.